Radiationsensitivityofplanarnpn structures, manufacturedonsilicon, isovalentlydopedwithgermanium (nSiGe) (Modern Problems of Metallurgy, 2019)
The doping by isovalent impurities (first of all, germanium (Ge)) has been proposed for increasing of the silicon radiation resistance.The most convenient structure for experimental measurements of h21E degradation under irradiation is a test npn transistor IC with dielectric isolation, the radiation degradation of which completely determined by the properties of a uniformly doped n-type SiGe single crystal wafer.The purpose of this work was a comparative assessment of the h21E degradation of ICs test npn structures, fabricated on nSiGe with different Ge concentrations and base widths to the action of α-radiation to confirm the technological applicability of isovalently doped Ge silicon for the formation of device structures that work in the fields of ionizing radiation.The measurements were carried out on the CZ-Si, orientation with ρ ≈ 0.2 Ω · cm, NOi ≈ 7 ∙ 1017 cm-3, NСi
Keywords: germanium-doped silicon; degradation of amplifying properties; test transistor; ionizing radiation